On the importance of studying and learning about the April 25, 1974, Revolution - Rezola, Maria Inácia (2020)
Capitulo introdutório ao livro coordenado por Paul Manuel Voices of the Revolution: Revisiting the Portuguese Revolution of 25 April 1974 - Interviews and Insights em que se traça um quadro genérico sobre a História e memória do 25 de Abril.